2021
DOI: 10.3892/mmr.2021.12329
|View full text |Cite
|
Sign up to set email alerts
|

Urantide prevents CCl4‑induced acute liver injury in rats by regulating the MAPK signalling pathway

Abstract: a number of drugs and other triggers can cause acute liver injury (ali) in clinical practice. Therefore, identifying a safe drug for the prevention of liver injury is important. The aim of the present study was to investigate the potential preventive effect and regulatory mechanism of urantide on carbon tetrachloride (ccl 4 )-induced ali by investigating the expression of components of the MaPK signalling pathway and the urotensin ii (uii)/urotensin receptor (uT) system. liver oedema and severe fatty degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…In this study, the DEGs in the livers between treated with and without MnCl 2 on the 1st and 3rd day were involved in MAPK signaling pathway (Fig. 3A-B), which was consistent with previous observations [41][42][43]. Li et al (2021) found that LPS could cause the liver damage, and MAPK signaling pathways might be involved in LPS-induced hepatotoxicity in geese [41].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the DEGs in the livers between treated with and without MnCl 2 on the 1st and 3rd day were involved in MAPK signaling pathway (Fig. 3A-B), which was consistent with previous observations [41][42][43]. Li et al (2021) found that LPS could cause the liver damage, and MAPK signaling pathways might be involved in LPS-induced hepatotoxicity in geese [41].…”
Section: Discussionsupporting
confidence: 92%
“…3A-B), which was consistent with previous observations [41][42][43]. Li et al (2021) found that LPS could cause the liver damage, and MAPK signaling pathways might be involved in LPS-induced hepatotoxicity in geese [41]. In addition, it may also be associated with ALI, and effective inhibition of the MAPK signaling pathway may be critical in protecting the liver from CCl 4 -induced ALI [42].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fibrosis produced in this way bears some resemblance to the mechanisms of hepatic fibrosis in humans (Crespo Yanguas et al, 2016). The first sign of liver injury and fibrosis, is the cellular release of liver enzymes which significantly increased within a short time (Li et al, 2021). According to our findings, inflammatory markers such as TNF-α significantly increase levels of liver enzymes like ALT and AST, which in turn caused an increase in the synthesis of collagen fibers within injured liver cells (Abdelghffar et al, 2022).…”
Section: Discussionmentioning
confidence: 51%
“…The MAPK protein family is activated via the phosphorylation of these proteins, which further activate transcription factors regulating the expression of target genes in the nucleus. In a previous study, urantide inhibited liver injury in vivo by inhibiting the MAPK signaling pathway [ 29 ]. In our study, the model group presented higher levels of phosphorylated JAK2 and phosphorylated p38 ( Figure 5 ), indicating the MAPK signaling pathway’s involvement in D-Gal-induced liver injury in vivo.…”
Section: Discussionmentioning
confidence: 99%